Utility of aPTT in Predicting 28-day Mortality in Septic AKI Patients - Parth Sharma; Pritam Singh; Nidhi Bhardwaj; Anita Tahlan (Apollo Medicine, 2026)
Background: Sepsis is an uncontrolled inflammation leading to multiple organ dysfunction. Septic acute kidney injury (AKI) is one of the leading causes of mortality. During sepsis, coagulation cascade derangement can occur. Score systems such as Acute Physiology and Chronic Health Evaluation II (APACHE-II) and Sequential Organ Failure Assesment have been developed, but they are not readily available in a resource-limited setting. Activated partial thromboplastin time (aPTT) and D-dimer can be used to prognosticate 28-day mortality in septic AKI patients. Patients and Method: This longitudinal observational study was conducted from March 2023 to September 2024 at the Medicine Emergency Department of the Department of General Medicine, Government Medical College and Hospital, Chandigarh. Patients diagnosed with sepsis as per the Sepsis 3.0 definition were screened for AKI using the Kidney Disease Improving Global Outcomes criteria. The blood investigations were sent, namely, serum electrolytes, renal function tests, liver function tests, complete blood count and coagulation profile. The results were analysed for 28-day in-hospital mortality. The main objective of our study was to determine the relationship between coagulation parameters and all-cause mortality in septic AKI patients. Results: Out of 63 patients with septic AKI, 38 (60.3%) were males, and 25 (39.7%) were females. The findings reveal that coagulation parameters of aPTT ≥80 seconds and D-dimer ≥6400 ng/mL have performance comparable to APACHE II and, therefore, can be used to predict 28-day mortality in patients with septic AKI. Conclusion: Our study revealed that aPTT and D-dimer can be used to predict 28-day mortality in septic AKI patients.